Banking and inequality: US state evidence. Issue 4 (1st December 2018) - Xu, Chen; Giedeman, Daniel C.; Compton, Ryan A.; Hoover, Gary A.
Abstract: The question of how financial development affects economic inequality is a subject of much debate. This paper adds to this literature by examining whether banking deregulation affects income inequality using state-level data from the United States from the late 20th century. Specifically, we test the hypothesis that the deregulation of interstate branch-banking restrictions had an effect on income inequality as measured by the Gini Coefficient and Thiel Index. We conduct our tests using fixed-effects OLS models and System GMM dynamic panel analysis. Our results suggest that branching deregulation has resulted in increased income inequality in the United States.